Kontribusi Sektor Informal dan Pariwisata dalam Kehidupan Sosial Ekonomi Masyarakat Lokal - Author: Fajriyanto (Universitas Islam Indonesia, 2006)
The role of tourism industry toward the activity of economy of local community is very important. But, not all tourism objects can contribute to local community optimally especially in the sector that needs formal conditions that difficult to conduct by informal sector of economy. In Indonesia cities, the tourism location is always closely related to informal sector of economy. For this reason, tourism location planning in cities in Indonesia need giving access and space to local community. This planning implies toward increasing the region income.